2021
DOI: 10.29333/pr/9665
|View full text |Cite
|
Sign up to set email alerts
|

Online Teaching and Learning of Higher Education in India during COVID-19 Emergency Lockdown

Abstract: The COVID-19 pandemic has generated a worldwide consciousness that the present way of lifestyle does not work. There are many areas need the revolutionary changes and it has become obvious, one among is educational sector. In India, educational institutes/universities remain closed since the mid of March-2020, because of the fast spread of COVID-19. Emergency lockdown has a preventive measure upended the life of students, parents and teachers. To combat this inevitable crisis educational sectors started conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…deficiencies are among the disadvantages of DE ( 19 ) . In the literature, it can be deduced that more than 60% of students are not ready for online classes due to poor network infrastructure and limited daily network data ( 24 ) . Another study reported that 65.8% of students experienced issues with their internet connection and the extra financial burden for internet quota caused further problems in DE ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…deficiencies are among the disadvantages of DE ( 19 ) . In the literature, it can be deduced that more than 60% of students are not ready for online classes due to poor network infrastructure and limited daily network data ( 24 ) . Another study reported that 65.8% of students experienced issues with their internet connection and the extra financial burden for internet quota caused further problems in DE ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and academics tried to understand students' perceptions on distance education during the COVID-19 pandemic and carried out empirical studies in India (Mishra et al, 2020;Naik et al, 2021), Serbia (Bojovic et al, 2020), Pakistan (Malik et al, 2020), USA (Aguilera-Hermida, 2020), South Africa (Armoed, 2021), Poland (Cicha et al, 2021), and elsewhere. According to the relevant literature, technological infrastructure and monetary issues are not the only important factors that differentiate the adaptation of the online learning procedures.…”
Section: Open Accessmentioning
confidence: 99%
“…During the pandemic, social media platforms are used to search for prevention and educational information to reduce the effect of this virus on many aspects of society (Khamis & Geng, 2021). Considering the challenges imposed on different societies because of the COVID-19 pandemic (Tesfamicael & Ayalew, 2021), many educational researchers agree that this pandemic has highlighted the important role that can be played by online teaching using social media in response to the emergency lockdowns of educational institutions (e.g., Naik et al, 2021).…”
Section: / 18mentioning
confidence: 99%